Factors associated with clinical failure of self-expandable metal stent for malignant gastroduodenal obstruction. (2nd January 2016) - Shin, Young Shin; Choi, Cheol Woong; Kang, Dae Hwan; Kim, Hyung Wook; Kim, Su Jin; Cho, Mong; Hwang, Sun Hwi; Lee, Si Hak
Abstract: Objective. Endoscopic self-expandable metal stent (SEMS) placement has emerged as an effective palliative treatment for inoperable malignant gastric outlet obstruction (GOO). In spite of successful stent placement, some patients complain of ongoing dysphagia and vomiting. Most reported data on SEMS to date are about technical success of different types of stents and low complication rates. The aim of this study was to evaluate the associated factors of clinical failure after endoscopic SEMS placement for inoperable malignant GOO. Methods. A total 122 patients who underwent successful endoscopic SEMS placement for malignant GOO in an academic referral center were included in the analyses. We retrospectively evaluated variables associated with clinical outcomes after successful SEMS placement. Results. The clinical success rate was 81.1%. The common causes of GOO were pancreatic (39%) and gastric cancers (32%). The mean length of the stents (± standard deviation) was 10.06 ± 2.42 cm. Multivariate analysis revealed that gallbladder cancer ( p = 0.016, OR 6.486, 95% CI, 1.509–59.655), poor performance status (ECOG ≥3) ( p = 0.001, OR 10.200, 95% CI, 2.435–42.721), the presence of carcinomatosis peritonei ( p < 0.001, OR 35.714, 95% CI, 5.556–250.000) and the failure of endoscope passage ( p = 0.039, OR 6.945, 95% CI, 1.101–43.818) Conclusion. Our results suggest that gallbladder cancer, poor performance status (ECOG ≥3) and the presence of carcinomatosis peritonei related with clinical failure of palliative SEMS placement.